2020
DOI: 10.1002/cnma.202000327
|View full text |Cite
|
Sign up to set email alerts
|

Structural, defect, transport and dopant properties of AgNbO3

Abstract: Silver niobate (AgNbO3) is a candidate lead‐free piezoelectric materials with potential applications in electronic technology and catalysis. Atomistic simulation techniques are used to examine the defects, diffusion of Ag+ and O2− ions, solution of dopants and electronic structures of pristine and doped configurations in AgNbO3. The Ag Frenkel is the most favourable intrinsic defect leading to the formation of Ag vacancies that can vehicle self‐diffusion of Ag+ ions in this material. The calculated activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
(46 reference statements)
0
5
0
1
Order By: Relevance
“…In this case of AgNbO 3 lms, the trap centers of carriers result from the defect complexes of V 0 Ag and V o , which keep the system more electrically insulating without exciting many free carriers at low electric eld. 53,63 This corresponds to the linear P-E loops with nearly zero remnant polarization and dielectric loss below an electric eld of 70 kV cm À1 , as well as low leakage current below an electric eld of 15 kV cm À1 as shown in Fig. 7(a)-(c).…”
Section: Electrical Propertiesmentioning
confidence: 72%
See 2 more Smart Citations
“…In this case of AgNbO 3 lms, the trap centers of carriers result from the defect complexes of V 0 Ag and V o , which keep the system more electrically insulating without exciting many free carriers at low electric eld. 53,63 This corresponds to the linear P-E loops with nearly zero remnant polarization and dielectric loss below an electric eld of 70 kV cm À1 , as well as low leakage current below an electric eld of 15 kV cm À1 as shown in Fig. 7(a)-(c).…”
Section: Electrical Propertiesmentioning
confidence: 72%
“…Moreover, the [] defect complex is likely to form due to the low formation energy supported by the first principles calculations. 53…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The E b is known as an extrinsic parameter that depends on factors such as relative density, average grain size, secondary phases, condition of test, thickness, electrodes, voltage type, band gap, etc. 6,20,79,80 Regarding the sample thickness, it should be noted that it is an effective parameter for E b , and thus an extremely high E b for thin films can be seen, which results in a high W rec . 34 In addition, Luo et al 4 showed that the breakdown strength improved with the addition of extra Ag 2 O, which is related to a decreased number of defects such as V′ Ag , V •• O , and their complexes.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…Por exemplo, se o raio iônico do cátion no sítio dodecaédrico é menor do que o raio iônico do íon hospedeiro (o íon Ag + nas composições estudadas), a estrutura perovskita pode ser compensada, devido à incompatibilidade no tamanho dos íons, pela inclinação dos octaedros NbO6 para atingir a estabilidade estrutural. Nesta situação, as ligações químicas Nb-O sofrerão uma compressão, com um aumento das tensões internas nas ligações Ag/La-O, a fim de compensar o excesso de espaço vazio na estrutura ABO3.Esta hipótese está em concordância com a tendência mostrada para o número de onda obtida para as amostras de ALNx (apresentado na tabela 2), que revelou um aumento do seu valor para os modos M8 e M9 e, consequentemente, as ligações Nb-O tornamse mais fortes como resultado da adição do lantânio para as composições modificadas.Uma rotação cooperativa dos octaedros NbO6 acomoda essas tensões induzidas pela variação na força das ligações A-O e B-O, o qual minimiza as interações eletrostáticas[138], levando de volta a uma inclinação dos octaedros de oxigênio para alcançar novamente a estabilidade estrutural. Isso pode significar que a inclinação/rotação octaédrica provoca uma estrutura ortorrômbica distorcida, o que sugere que o deslocamento do íon Nb 5+ desde sua posição cristalográfica centrada (na fase cúbica) é provavelmente maior, formando uma estrutura menos simétrica com o aumento da concentração de lantânio.…”
unclassified